Environmentally friendly technology for the modification of lubricants with graphene nanostructures - Alhilo, Z. A. А.; Zhumagalieva, G.; Pasko, T. (My University, 2020)
Nanomaterials, and in particular graphene, significantly increase the basic tribological characteristics of lubricants. One of the most effective ways to quickly use laboratory results on an industrial scale is to modify traditional lubricants with graphene concentrates. The research results showed that in order to solve this problem successfully, it is necessary to create graphene concentrate and distribute it evenly over the total volume of the lubricant. It is necessary that the concentrate be prepared on the same basis as the lubricant. In the present work, previous studies on the mechanical activation and exfoliation of graphite in a core drum mill, liquid-phase shear exfoliation in a rotary apparatus with moving blades, and the homogenization of graphene nanostructures in lubricants using a rotary mixer are combined. Changes were made to the design of the main components, taking into account the use of this technology in the industry. The presented technology is environmentally friendly, since only oil and graphite are used and there are no harmful wastes that must be disposed of. Наноматериалы, в частности графен, значительно повышают основные трибологические характеристики смазок. Один из наиболее эффективных способов быстро использовать результаты лабораторных исследований в промышленных масштабах - это модифицировать традиционные смазочные материалы с помощью графеновых концентратов. Результаты исследований показали, что для успешного решения этой задачи необходимо создать концентрат графена и равномерно распределить его по всему объему смазки. Необходимо, чтобы концентрат готовился на той же основе, что и смазка. В настоящей работе объединены предыдущие исследования механической активации и расслоения графита в стержневой барабанной мельнице, жидкофазного расслоения при сдвиге во вращающемся аппарате с движущимися лопастями и гомогенизации графеновых наноструктур в смазочных материалах с помощью роторного смесителя. Изменения внесены в конструкцию основных компонентов с учетом использования данной технологии в промышленности. Представленная технология экологически чистая, так как используются только масло и графит и отсутствуют вредные отходы, которые необходимо утилизировать.
International Scientific Practical Conference on Materials Science, Shape-Generating Technologies and Equipment (ICMSSTE 25-29 May 2020
Keywords: импакт-фактор 2020; томсон; кларивате аналитикс; конференции; зарубежное издание; зарубежные авторы; смазочные материалы; графеновые концентраты; графен; графит